(untitled) (INNOVATIVE ECONOMY, 2023)
Zvarych R.Ye., Khomenska I.V., Seheda O.O. DETERMINANTS OF UKRAINE’S ECONOMIC PARTNERSHIP WITH COUNTRIES OF THE MIDDLE EAST IN THE CONTEXT OF PUBLIC DIPLOMACY DEVELOPMENT Purpose. The aim of the article is to study of the main factors affecting the formation of economic partnership of Ukraine with the countries of the Middle East in the context of the growing role of public diplomacy. Methodology of research. The methodological basis of the research was the scientific works of scientists on the problems of economic partnership and public diplomacy. General scientific and special methods were used in the research process, in particular: dialectical, monographic and systemic analysis – to substantiate the essence of the functioning of modern diplomacy; analysis and synthesis – for studying the object and subject of research; abstract and logical – during the formation of theoretical generalizations, assumptions, conclusions. Findings. The main factors affecting the development of Ukraine’s economic partnership with the countries of the Middle East, including trade, investment, energy, tourism and other areas were determined. Assessment of the impact of public diplomacy on the formation and development of economic partnership, in particular, the identification of successful examples and strategies was conducted. The multifaceted nature of cooperation between Ukraine and the countries of the Middle East is analysed. Opportunities for further development of economic partnership and identification of challenges faced by Ukraine in this region were identified. Based on the results of the analysis, recommendations were made regarding the use of public diplomacy tools to promote effective cooperation between Ukraine and the countries of the Middle East. Originality. The determinants of Ukraine’s economic partnership with the countries of the Middle East are considered in the context of public diplomacy, which, unlike the existing one, will contribute to a deeper understanding of the interdependence and mutual influence of political and economic factors in international relations. The study of the complex of factors influencing the development of economic partnership has been further developed, taking into account the specifics of the countries of the Middle East and their relations with Ukraine due to the influence of public diplomacy on the formation and improvement of economic partnership, as well as the identification of effective practices of using public diplomacy to intensify cooperation between countries and ensure their social and economic development. The sequence of development of the public diplomacy plan of the country, which will take into account the peculiarities of the region, is proposed. Practical value. The results of the study will provide the subjects of public diplomacy with the opportunity to analyse and improve cooperation strategies with the countries of the Middle East, which will contribute to the improvement of economic indicators and the development of trade, investment and cultural relations. Analysis of the determinants of economic partnership and developed recommendations will improve external communication through the channels of public diplomacy of Ukraine and form a positive perception of the country as a reliable and attractive partner for cooperation. Recommendations on optimizing economic partnership strategies will help in creating a favourable investment climate, attracting foreign investors and expanding business opportunities in the Middle East region and improving social and economic indicators. The suggestions made regarding the importance of intensifying cultural and educational projects between Ukraine and the countries of the Middle East can be used in building reliable economic relations between partners.